2019
DOI: 10.12799/jkachn.2019.30.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Instrument to Measure Nursing Information Literacy Competency

Abstract: The purpose of this study was to develop an instrument for measuring nursing information literacy competency, and then to examine the validity and reliability of the instrument. Methods: The developmental process of the instrument includes construction of a conceptual framework, generation of initial items, verification of content validity, preliminary study, extraction of final items, and psychometric testing. Its content validity was verified by three experts from nursing and nursing informatics. Its constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…For the noun topics identified in the present study, the questions were classified into categories of pediatric diabetes, gestational diabetes, and diabetes in older individuals, depending on the stage of life to which the question pertained. Such findings were consistent with a study on a needs survey for providing health information conducted on an Internet panel group, which reported that different population groups of respondents showed different preferences for health information [56]. This may be due to the characteristics of people who use online health information.…”
Section: Discussionsupporting
confidence: 90%
“…For the noun topics identified in the present study, the questions were classified into categories of pediatric diabetes, gestational diabetes, and diabetes in older individuals, depending on the stage of life to which the question pertained. Such findings were consistent with a study on a needs survey for providing health information conducted on an Internet panel group, which reported that different population groups of respondents showed different preferences for health information [56]. This may be due to the characteristics of people who use online health information.…”
Section: Discussionsupporting
confidence: 90%
“…Various scales have been developed to assess the level of NI competencies in the English language [3]. The Self-Assessment of Nursing Informatics Competencies Scale (SANICS) [4] has been demonstrated to have sound psychometric properties.…”
Section: Introductionmentioning
confidence: 99%